2013
DOI: 10.1016/j.jvs.2012.09.083
|View full text |Cite
|
Sign up to set email alerts
|

The Comprehensive Risk Assessment for Bypass (CRAB) facilitates efficient perioperative risk assessment for patients with critical limb ischemia

Abstract: The CRAB is a CLI-specific, risk assessment instrument derived from multi-institutional American College of Surgeons-National Surgical Quality Improvement Program surgical outcomes data that out-performs existing prognostic risk indices in the prediction of clinically significant adverse events after bypass surgery. Use of the CRAB as a risk assessment tool provides an evidence basis for patient-centered clinical decision making and may have a role in identifying patients at higher risk for surgical revascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 21 publications
4
39
1
10
Order By: Relevance
“…It is not surprising that functional dependence is a predictor of poor outcomes in CFE as it a known predictor of morbidity and mortality in lower extremity bypass. 21,22 Likewise dyspnea at Abbreviations: CI, confidence interval; OR, odds ratio. rest has also been associated with an increased risk of postoperative mortality.…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that functional dependence is a predictor of poor outcomes in CFE as it a known predictor of morbidity and mortality in lower extremity bypass. 21,22 Likewise dyspnea at Abbreviations: CI, confidence interval; OR, odds ratio. rest has also been associated with an increased risk of postoperative mortality.…”
Section: Discussionmentioning
confidence: 99%
“…9) Other authors tried to create a prognostic score for the saphenous vein bypass (CRAB); the considered factors were: age >75 years, prior amputation/revascularization, ulceration, hemodialysis, recent angina, emergent case, partial/total functional dependence. 10) On the other hand, the main factor associated with late failure of prosthetic graft has been supposed to be dependent on the intrinsic thrombogenicity of synthetic materials, along with the miointimal hyperplasia at the anastomotic sites and the progression of atherosclerosis on inflow and outflow vessels.…”
Section: Review Articlementioning
confidence: 99%
“…Our group has previously published a more comprehensive, targeted risk assessment tool to predict 30-day major morbidity and mortality after bypass surgery for CLI; The Comprehensive Risk Assessment for Bypass 6. A review of the American College of Surgeons-National Surgical Quality Improvement Program (ACS-NSQIP) found that the 30-day mortality rate after lower extremity bypass for CLI was 2.9%, with a major morbidity at a rate of 19.1% 6.…”
Section: Perioperative Risk Assessmentmentioning
confidence: 99%
“…A review of the American College of Surgeons-National Surgical Quality Improvement Program (ACS-NSQIP) found that the 30-day mortality rate after lower extremity bypass for CLI was 2.9%, with a major morbidity at a rate of 19.1% 6. The composite major morbidity and mortality end point was seen in 10.1% of patients.…”
Section: Perioperative Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation